DR-5 and DLL-4 mAb Functionalized SLNs of Gamma-Secretase Inhibitors- An Approach for TNBC Treatment - Mamta Kumari; Praveen T. Krishnamurthy; Sai kiran S. S. Pinduprolu; Piyongsola Sola (Tabriz University of Medical Sciences, 2021)
Triple-negative breast cancer (TNBC) is the most aggressive and heterogeneous cancer subtypes. High rates of metastasis, poor prognosis, and drug resistance are the major problems associated with TNBC. The current chemotherapeutics eliminate only the bulk tumor cells (non-BCSCs) and do not affect breast cancer stem cells (BCSCs). The BCSCs which are left behind after chemotherapy is reported to promote recurrence and metastasis of TNBC. Death receptor-5 (DR-5) is exclusively expressed in TNBCs and mediates the extrinsic pathway of apoptosis. DR-5, therefore, can be exploited for targeted drug delivery and to induce apoptosis. Gamma-secretase mediated Notch signaling in BCSCs regulates its proliferation, differentiation, and metastasis. The endogenous ligand, Delta-like ligand 4 (DLL4), is reported to activate this Notch signaling in TNBC. Blocking this signaling pathway using both gamma-secretase inhibitors (GSIs) and DLL4 monoclonal antibody (mAb) may produce synergistic benefits. Further, the GSIs (DAPT, LY-411575, RO4929097, MK0752, etc.) suffer from poor bioavailability and off-target side effects such as diarrhea, suppression of lymphopoiesis, headache, hypertension, fatigue, and ventricular dysfunctions. In this hypothesis, we discuss Solid lipid nanoparticles (SLNs) based drug delivery systems containing GSIs and surface modified with DR-5 and DLL4 monoclonal antibodies (mAb) to effectivity target and treat TNBC. The delivery system is designed to deliver the drug cargo precisely to TNBCs through its DR-5 receptors and hence expected to reduce the off-target side effects of GSIs. Further, DLL4 mAb and GSIs are expected to act synergistically to block the Notch signal mediated BCSCs proliferation, differentiation, and metastasis.